2010
DOI: 10.4236/cs.2010.12012
|View full text |Cite
|
Sign up to set email alerts
|

New Communication Bands Generated by Using a Soliton Pulse within a Resonator System

Abstract: We propose a novel system of a broadband source generation using a common soliton pulse (i.e. with center wavelength at 1.55 m) propagating within a nonlinear microring and nanoring resonators system. A system consists of a micro ring resonator system incorporating an add/drop filter, whereas the large bandwidth signals can be generated, stored and regenerated within the system. By using the appropriate parameters relating to the practical device such as micro ring radii, coupling coefficients, linear and non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 8 publications
0
15
0
Order By: Relevance
“…This means that we can employ the dark soliton penalty because of the low level of the peak power to be the benefit, where the predicting idea is that a dark soliton can perform the communication transmission carrier where the recovery can be retrieved by the darkbright soliton conversion [5]. A soliton pulse can be localized among a waveguide consists of micro and nanoring resonator, hence the soliton pulse can be stored within the nano-waveguide [6]. We have shown that the dark soliton can be input and chopped to the noisy signals for security use within the nonlinear ring resonator system [7].…”
Section: Introductionmentioning
confidence: 99%
“…This means that we can employ the dark soliton penalty because of the low level of the peak power to be the benefit, where the predicting idea is that a dark soliton can perform the communication transmission carrier where the recovery can be retrieved by the darkbright soliton conversion [5]. A soliton pulse can be localized among a waveguide consists of micro and nanoring resonator, hence the soliton pulse can be stored within the nano-waveguide [6]. We have shown that the dark soliton can be input and chopped to the noisy signals for security use within the nonlinear ring resonator system [7].…”
Section: Introductionmentioning
confidence: 99%
“…The methodology of this study can be performed by configuration and using of an interferometer add/drop filter system connecting to series of microring resonators [45]. Variation of the system's parameters affect the output results in which tuned and amplified optical tweezers can be generated.…”
Section: Theoretical Modeling and Research Methodologymentioning
confidence: 99%
“…To generate a spectrum of light over a broad range [3], an optical soliton pulse is recommended as a powerful laser pulse that can be used to generate chaotic filter characteristics when propagating within nonlinear MRRs [4][5][6][7]. Using this technique, the capacity of the transmission data [8] can be secured and increased when the chaotic packet switching is employed [9]. This system is used to trap optical solitons in order to generate entangled photon pair required for CVQKD [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%